The Relationship between Learning Organizations and Professional Commitment with Innovation - Sastrawijaya, Ade (CV. Rayyan Dwi Bharata, 2025)
This research explains the relationship between learning organizations and professional commitment to innovation. The research method uses a correlational method with a quantitative approach. The population was 205 Package B tutors equivalent to junior high schools in Cirebon City with a sample of 127 people. The results of this research are: 1) there is a relationship between learning organizations and innovation, with a value of r = 0.47, R2 = 22.60%. 2) there is a relationship between professional commitment to innovation with a value of r = 0.41, R2 = 17.50%. 3) there is a simultaneous relationship between learning organizations and professional commitment to innovation, with a value of r = 0.48, R2 = 23.80%. The results obtained can provide an illustration that tutor innovation can be improved by increasing discipline, systems thinking, having personal expertise that can be shared with colleagues and supported by a high sense of obligation, being committed to the profession and having the awareness to continue to be in the organization by showing performance. the high one. The conclusion of this research is that there is a relationship between learning organizations and professional commitment, both partially and simultaneously, towards tutor innovation.